Acceptability and use of glaucoma virtual clinics in the UK: a national survey of clinical leads. Issue 1 (16th February 2018) - Gunn, Patrick J G; Marks, Joanne R; Au, Leon; Waterman, Heather; Spry, Paul G D; Harper, Robert A
Abstract : Objective: The purpose of this paper is to describe the findings of a national survey that aimed to estimate the proportion of Hospital Eye Service (HES) units using glaucoma virtual clinics, to determine how these services differ and to gauge clinicians' views and opinions on the safety and acceptability of this model of care compared with usual care. Methods and analysis: This 12-question survey was disseminated nationally to 92 clinical lead consultant ophthalmologists using SurveyMonkey. Results: The response rate was 45.7%. There were 21 out of the total 42 respondents (50.0%) who were based at an NHS Trust where glaucoma virtual clinics were already being used and a further 9 (21.4%) were planning to establish one. Clinical leads largely rated efficiency and patient safety to be at least equivalent to usual care (92.9%) and 81.0% perceived glaucoma virtual clinics to be acceptable to patients. The main reasons for not running glaucoma virtual clinics were insufficient staff (71.4%) and inadequate space (47.6%). The majority of those running virtual clinics used this model of care for 'lower risk' patients such as ocular hypertensives (90.5%) and glaucoma suspects. Conclusion: Glaucoma virtual clinics are employed by a large proportion of HES units, with many seeking to develop such services. Clinical leads largely rate efficiency, patient safety and the perception of patient acceptability to be at least equivalent to usual care.